Perencanaan Koefisien Reduksi Bearing Capacity Pondasi Dangkal akibat Fluktuasi Muka Air Tanah - Fitria Wulandari, Fadila (Teknik Sipil, Politeknik Negeri Ketapangg, 2023)
The rapid development of infrastructure in Indonesia, especially in the field of housing, has made people interested in developing multi-level housing, including in Tegal Gondo Village, Karangploso District, Malang Regency because of its geographical location which borders Malang City and has great potential as a supporting area. However, the condition of the soil which has very varied fluctuations (rising and falling) of the ground water level during the rainy and dry seasons is considered dangerous because several houses showed cracks in the sloof and walls during the initial study. So it is necessary to plan the reduction coefficient of soil bearing capacity for planning shallow foundations for simple dwellings. This planning was translated into three stages of activity, namely data collection, laboratory testing, and data processing using Plaxis Version 8.2 software which was confirmed using manual calculations using the Terzaghi formula. Variations in soil depth were taken at -1.00 m and -2.00 m with a 1.00 x 1.00 square shallow foundation design model. The results of the researchyielded a φR value (reduction number of bearing capacity) of 0.64 from an average bearing capacity of 66.13 tons/m2 at a depth of -1.00 m. In addition, at a depth of -2.00 m it has a φR value (reduction number of bearing capacity) of 0.55 from an average carrying capacity of 105.78 tons/m2.